Apoptotic cell death via oxidative stress mediated caspase-dependent mechanism in Jurkat T cells by cardamonin and its transition metal Cu (II) and Fe (II) complexes - Khoo, Yi Vonn (2018)
Cancer is a leading cause of death worldwide as cancer cells have the ability to develop resistance to chemotherapeutic agents due to their high expressions of resistance gene. More research on alternative strategies to eradicate this type of malignant cells is highly desired by using natural products with fewer side effects. This study initially investigates the cytotoxicity of 20 novel semi-synthetic cardamonin derivatives and complexes in A549 lung and HK1 nasopharyngeal cancer cell lines. Structure activity relationship analysis revealed the factors affecting cytotoxicity were modification of hydroxyl group, presence of alkene group, addition of chemical groups, with the greatest cytotoxicity advantage being complexing with metal ions. Cardamonin-Cu(II) and cardamonin-Fe(II) complexes were determined as the two most cytotoxic compounds and were selected for further cytotoxic analysis in normal MRC5 lung and normal Hs68 foreskin cell lines. Results showed toxicity in MRC5 lung cells but was less toxic in Hs68 foreskin cells, suggesting some level of selectivity from cardamonin, cardamonin-Cu(II) and cardamonin-Fe(II) depending on the type of cells exposed to. Subsequently, cardamonin and its two complexes were tested in Jurkat T leukaemic cells and results showed highest susceptibility in this leukaemic cell line prompting further investigation on differential susceptibility of adherent and suspension cells. THP-1 monocytic leukaemia cell line cultured in both suspension and adherent phase demonstrated increased resistance in THP-1-derived macrophages in adherent phase compared to THP-1 monocytes in suspension form. Herein, we investigated the effects of interference from inhibitors of p38α and p38β MAP kinase and found THP-1-derived macrophages’ increased resistant towards cardamonin, cardamonin-Cu(II) and cardamonin-Fe(II) complexes were independent of p38α and p38β MAP kinase pathway. As Jurkat T cells exhibited lowest IC50 values in cardamonin, cardamonin-Cu(II) and cardamonin-Fe(II)-treated cells, we next explored the underlying mechanism of action in this cell. All three compounds were found to induce apoptotic cell death via the intrinsic mitochondrial pathway in Jurkat T cells as evidenced by the morphological changes, phosphatidylserine externalisation, caspase-3, -9 and PARP-1 cleavage, and collapse of mitochondrial membrane potential. Caspase-8, an initiator caspase of the extrinsic pathway was not activated. The presence of a caspase inhibitor, Z-VAD-FMK, was able to inhibit caspase processing and block cell death, further confirming the induced apoptotic cell death was caspase-dependent. As previous studies have reported the ability of metals to induce apoptosis through oxidative stress, the effects of these three compounds on reactive oxygen species (ROS) generation and intracellular glutathione (GSH) levels were explored. Results revealed cardamonin and cardamonin-Fe(II)-induced depletion of intracellular GSH and production of ROS; whereas cardamonin-Cu(II) did not significantly affect intracellular GSH levels but generated ROS. The presence of low molecular weight thiols, N-acetylcysteine (NAC), L-cysteine and GSH as well as Trolox, a ROS scavenger, blocked cardamonin and cardamonin-Fe(II)-induced Jurkat T cell death, while D-cysteine, which cannot be metabolised to GSH had no effect. However, these low molecular weight thiols had no effect on cardamonin-Cu(II)- treated cells with the exception of Trolox, confirming the role of ROS in cardamonin- Cu(II)-induced Jurkat T cell death. Furthermore, intracellular ROS and GSH levels were recovered close to levels of untreated Jurkat T cells in the presence of Z-VAD- FMK. In conclusion, this study demonstrates cardamonin, cardamonin-Cu(II) and cardamonin-Fe(II) induced apoptotic cell death in Jurkat T cells via an oxidative stress mediated intrinsic mitochondrial pathway that was caspase-dependent.